2017
DOI: 10.1186/s40352-017-0048-z
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability and effectiveness of a web-based psychosocial intervention among criminal justice involved adults

Abstract: BackgroundThe acceptability, feasibility and effectiveness of web-based interventions among criminal justice involved populations are understudied. This study is a secondary analysis of baseline characteristics associated with criminal justice system (CJS) status as treatment outcome moderators among participants enrolling in a large randomized trial of a web-based psychosocial intervention (Therapeutic Education System [TES]) as part of outpatient addiction treatment.MethodsWe compared demographic and clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 33 publications
0
16
0
1
Order By: Relevance
“…This study found that participants who received TES as part of their care model had a markedly lower rate of treatment dropout (hazard ratio = 0.72, 95% CI = 0.57, 0.92) and a higher rate of drug abstinence (odds ratio = 1.62, 95% CI = 1.12, 2.35), an effect that was most evident among patients who had a drug-positive urine and/or alcohol-positive breath screen at the time of entering the study (odds ratio = 2.18, 95% CI = 1.30, 3.68). This pattern highlighting the effectiveness of TES was across diverse groups of patients, including those with stimulant, cannabis and alcohol use disorders (Cochran et al, 2015), those with and without criminal justice involvement (Lee et al, 2017) those with and without Internet access (Tofighi et al, 2016), and across both males and females and diverse racial and ethnic groups (Campbell et al, 2017). TES was also found to have promising cost-effectiveness (Murphy et al, 2016).…”
Section: Ctn Studies That Employed Digital Therapeuticsmentioning
confidence: 88%
“…This study found that participants who received TES as part of their care model had a markedly lower rate of treatment dropout (hazard ratio = 0.72, 95% CI = 0.57, 0.92) and a higher rate of drug abstinence (odds ratio = 1.62, 95% CI = 1.12, 2.35), an effect that was most evident among patients who had a drug-positive urine and/or alcohol-positive breath screen at the time of entering the study (odds ratio = 2.18, 95% CI = 1.30, 3.68). This pattern highlighting the effectiveness of TES was across diverse groups of patients, including those with stimulant, cannabis and alcohol use disorders (Cochran et al, 2015), those with and without criminal justice involvement (Lee et al, 2017) those with and without Internet access (Tofighi et al, 2016), and across both males and females and diverse racial and ethnic groups (Campbell et al, 2017). TES was also found to have promising cost-effectiveness (Murphy et al, 2016).…”
Section: Ctn Studies That Employed Digital Therapeuticsmentioning
confidence: 88%
“…The same trend seems to be recognizable in research on web-based intervention in forensic psychiatry: a review identified nine studies that focused on evaluation of different types of text-based digital interventions ( 14 ). Seven of those showed outcomes at least as effective as comparison groups and more effective than no intervention groups ( 16 , 35 – 40 ), while only two studies found no improvements ( 41 , 42 ). Consequently, psycho-education or standardized assignments in face-to-face treatment might be replaced by eHealth interventions, which could take valuable time of therapists' hands and provide them with more room for in-depth treatment.…”
Section: Ehealth and The Risk-principlementioning
confidence: 99%
“…The most prominent intervention type was medications for opioid use disorder (MOUD), comprising nearly 35% ( n = 20) of the total sample. Thirteen articles (22.4%) examined interventions that emphasized peer support or social support systems, nine articles (15.5%) examined case management approaches, and seven articles (12%) examined behavioral therapies like cognitive behavioral therapy ( Lee et al, 2017 ), dialectical behavioral therapy ( Nyamathi et al, 2017b , Nyamathi et al, 2017a ), motivational interviewing ( Polcin et al, 2018 ), contingency management ( Lee et al, 2017 ), and individual, family, or group therapy ( Miller et al, 2017 , McHugo et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“… Kelly et al, 2020 . Friese and Wilson, 2021 ; Lee et al, 2017 ; Maruca et al, 2021 ; Morse et al, 2021 ; Reingle Gonzalez et al, 2019 . Note.…”
Section: Resultsunclassified